2001
DOI: 10.1665/1082-6467(2001)010[0347:aolagt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of locusts and grasshoppers to the low and variable rainfall of Australia

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 9 publications
1
31
0
2
Order By: Relevance
“…The greater diversity of Orthoptera recorded in Koléa station, where the winter minima temperatures are milder, fit with the preliminary results of Petit and Benfekih (2009), but long-term studies of meteorological parameters and Orthoptera dynamics should be undertaken to arrive at sound conclusions (Carter et al, 1998;Cigliano et al, 2002;Hunter et al, 2001;Köhler et al, 1999).…”
Section: Influence Of Climatic Constraints On Assemblagessupporting
confidence: 72%
“…The greater diversity of Orthoptera recorded in Koléa station, where the winter minima temperatures are milder, fit with the preliminary results of Petit and Benfekih (2009), but long-term studies of meteorological parameters and Orthoptera dynamics should be undertaken to arrive at sound conclusions (Carter et al, 1998;Cigliano et al, 2002;Hunter et al, 2001;Köhler et al, 1999).…”
Section: Influence Of Climatic Constraints On Assemblagessupporting
confidence: 72%
“…In some scenarios, livestock grazing increased grasshopper abundance and decreased species diversity (Joern 2004), whereas other studies found the opposite (Capinera and Sechrist 1982;Jepson-Innes and Bock 1989;Quinn and Walgenbach 1990;Onsager 2000). Likewise, precipitation and temperature had varying effects (Johnson and Worobec 1988;Kemp and Cigliano 1994;Ovadia and Schmitz 2004;Jonas and Joern 2007;Powell et al 2007;Gardiner 2010;Hunter et al 2010). The influence of grazing and precipitation on grasshopper communities may vary among sites, years, grasshopper species and vegetation assemblages, making these relationships complex and nuanced (Capinera and Horton 1989).…”
Section: Introductionmentioning
confidence: 99%
“…C. terminifera outbreaks occur following rainfall during the warmer months in the Mitchell grasslands of the arid and semi‐arid interior (Australian Plague Locust Commission 1986; Wright 1987; Hunter 1989; Hunter, Walker & Elder 2001). Population dynamics are influenced by the ability of the locusts to use the growth of grass resulting from a single rainfall event to complete nymphal development and migrate.…”
Section: Introductionmentioning
confidence: 99%
“…Plagues are more likely to develop following high rainfall and this has been attributed to the extended period of D. radulans availability (Hunter 1989). Grass growth follows one rainfall event, and as follow‐up rain rarely falls (Hunter et al . 2001), locusts that have not completed their nymphal development are forced to switch to the perennial A. lappacea as D. radulans dies off.…”
Section: Introductionmentioning
confidence: 99%